Da'wah Message In Surah Al-A'raf Verse 85 (Semiotic Analysis Of Roman Jakobson) - Sharikhul Hanif; Hasan Basri; Muhammad Irsyad (Journal Analytica Islamica, 2023)
Surah Al-A'raf Verse 85 of the Al-Qur'an is one of the verses that contains a strong message of preaching in Islam. This research aims to understand the message of da'wah in this verse by applying Roman Jakobson's semiotic approach, which allows analysis of communication elements and language structures in this sacred text. The research method used in this research is using a type of library research with a content analysis approach. This research is supported by the use of data collection techniques in the form of: reading and understanding the message of da'wah in surah Al-A'raf verse 85 with analysis of Roman Jakobson's semiotics and its relevance to the modern context. The results of the study show that the message of da'wah in Surah Al-A'raf Verse: 85 contains elements of communication, such as the sender of the message (Prophet Syu'aib AS), the message (call for monotheism and rejection of idol worship), the recipient of the message (the Madyan ), communication codes (Arabic), communication channels (Qur'anic texts), and the historical context surrounding them. The message of da'wah has strong relevance in modern society. The message of monotheism and rejection of idol worship remains central to Islamic teachings and influences the thinking, morals and behavior of individual Muslims. Additionally, Roman Jakobson's semiotic analysis helps us understand how Arabic was used specifically to convey this message with clarity and power.Surah Al-A'raf Ayat 85 dari Al-Qur'an adalah salah satu ayat yang mengandung pesan dakwah yang kuat dalam Islam. Penelitian ini bertujuan untuk memahami pesan dakwah dalam ayat ini dengan menerapkan pendekatan semiotika Roman Jakobson, yang memungkinkan analisis elemen-elemen komunikasi dan struktur bahasa dalam teks suci ini. Adapun metode penelitian yang digunakan pada penelitian ini adalah dengan menggunakan jenis penelitian kepustakaan (Library research) dengan pendekatan content analysis. Penelitian ini didukung dengan penggunaan teknik pengumpulan data berupa: membaca dan memahami pesan dakwah dalam surah Al-A'raf ayat 85 dengan analisis Semiotika Roman Jakobson dan relevansinya terhadap konteks modern.Hasil penelitian menunjukkan bahwa pesan dakwah dalam Surah Al-A'raf Ayat: 85 terdapat unsur-unsur komunikasi, seperti pengirim pesan (Nabi Syu'aib AS), pesan (seruan untuk tauhid dan penolakan terhadap penyembahan berhala), penerima pesan (kaum Madyan), kode komunikasi (bahasa Arab), saluran komunikasi (teks Al-Qur'an), dan konteks historis yang mengitarinya. Pesan dakwah memiliki relevansi yang kuat dalam masyarakat modern. Pesan tentang tauhid dan penolakan terhadap penyembahan berhala tetap menjadi inti ajaran Islam dan memengaruhi pemikiran, moral, dan perilaku individu Muslim. Selain itu, analisis semiotika Roman Jakobson membantu kita memahami bagaimana bahasa Arab digunakan secara khusus untuk menyampaikan pesan ini dengan kejelasan dan kekuatan.